Cost-benefit analysis of options for the 470 – 694 MHz spectrum band - Kalvin Bahia; Francisco Amaya (International Telecommunications Society (ITS), 2023)
Considerations on the optimal approach for managing spectrum are currently at the forefront of the debate around the sub-1 GHz frequency range between the 470-694 MHz, as Governments decide how best to manage this spectrum over the coming years. We apply a cost-benefit analysis in three synthetic countries in Europe, the Middle East and Africa countries to identify the policies that will maximise the social and economic value of this spectrum. We find that assigning 80 MHz additional of UHF spectrum to mobile would be 6-24 times greater than the costs incurred by the broadcasting sector to maintain the existing number of digital terrestrial television (DTT) programmes. Additionally, in a scenario where the full 470-694 MHz band is assigned to mobile, the benefits are 4-9 times greater for a typical country in Europe and the Middle East. This reflects the growing demand for 5G bandwidth and the general decline in DTT, driven in significant part by the rise of IPTV and on-demand viewing. The results therefore show that the utilisation of more UHF spectrum for mobile use will provide greater value to society than maintaining it for broadcasting.
Keywords: D61; L51; L96; 330